PEMBELAJARAN BAHASA ARAB DENGAN METODE JIGSAW UNTUK SANTRI KELAS VIII DI PONDOK PESANTREN AR RIYADH PANGKALAN BALAI - Adha, Ashabul; Ahmad Tarmizi; Nazarmanto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine the effectiveness of the Jigsaw method in Arabic language learning among Grade VIII students at Pondok Pesantren Ar Riyadh Pangkalan Balai. The research was driven by the low participation and limited comprehension of students during teacher-centered instruction. Using a mixed-methods approach, data were collected through observations, interviews, documentation, and pre-test and post-test assessments. The Jigsaw method was implemented through structured stages involving home groups, expert groups, discussion, presentation, and individual evaluation. Data analysis was carried out using SPSS, including normality tests and paired sample t-tests, complemented by N-Gain calculations to measure learning improvement. The results indicate that the Jigsaw method successfully enhanced students’ engagement, collaboration, and confidence in understanding the learning material. Quantitatively, the average score increased from 51 in the pre-test to 90.5 in the post-test. Statistical results confirmed a significant difference between the two scores, with an N-Gain value of 0.80 categorized as high. These findings demonstrate that the Jigsaw method is effective in improving learning outcomes and the overall quality of Arabic language learning at Pondok Pesantren Ar Riyadh Pangkalan Balai.